Effect of Compensation, Workload, Leadership on Employee Performance and Implications on Organizational Performance - Agustina Anisa; Yuliantini Tine (Publikasi Indonesia, 2022)
Discussing the practice of human resource management, one of the things that makes the determining factor for the company's success is performance. The same is true for the services business sector of PT Pelita Indonesia Djaya, to become a company that has a good reputation when providing services, performance is also considered important. This study aims to analyze the effect of Compensation, Workload, Leadership on Employee Performance and Implications on Organizational Performance Case study PT Pelita Indonesia Djaya. This research methodology uses a quantitative approach method using Smart PLS 3.3.9 to analyze several theoretical concepts to 88 respondents of company employees. Based on the results of the analysis in this study, the results obtained are that: 1) There is a positive and significant effect of compensation on employee performance; 2) There is a significant and significant effect of Workload on Employee Performance; 3) There is a positive and significant influence of leadership on employee performance; 4) There is a positive and significant effect of Compensation on Organizational Performance; 5) There is a significant and influential workload on Organizational Performance; 6) There is a positive and significant influence of Leadership on Organizational Performance; 7) There is a positive and significant effect of Employee Performance on Organizational Performance; 8) There is a positive and significant effect of Compensation on Organizational Performance through Employee Performance; 9) There is a significant and significant influence on Organizational Performance Workload through Employee Performance; 10) There is a positive and significant influence of Leadership on Organizational Performance through Employee Performance.